2016
DOI: 10.1159/000458726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maxing Shigan Tang on H1N1 Influenza A Virus-Associated Acute Lung Injury in Mice

Abstract: Objective: This study is aimed at examining the effects of Maxing Shigan Tang (MST) treatment on H1N1-associated acute lung injury (ALI) and exploring the possible mechanism. Material and Methods: Mice were randomly divided into a control group, model group, peroxisomal proliferator activator receptor γ (PPARγ) inhibition group (PPARγ-), PPARγ activation group (PPARγ+), and MST group. Influenza A (H1N1) virus of the Fort Monmouth 1 (FM1) strain was used to induce an ALI mice model. Hematoxylin and eosin staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This formula has been widely applied for the treatment of colds, influenza, acute bronchitis, bronchial asthma, and chronic obstructive pulmonary disease [14] . The clinical study also showed a positive effect for the patient with H1N1 influenza virus infection [15] , and its ability to alleviate the virus-induced lung injury has attracted more and more research interest [16] , [17] . Therefore, this formula has been recommended as one of the prescriptions for the COVID-19 treatment and has been proved to be beneficial to cure respiratory tract diseases with symptoms of fever, cough, short breath, and body ache, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…This formula has been widely applied for the treatment of colds, influenza, acute bronchitis, bronchial asthma, and chronic obstructive pulmonary disease [14] . The clinical study also showed a positive effect for the patient with H1N1 influenza virus infection [15] , and its ability to alleviate the virus-induced lung injury has attracted more and more research interest [16] , [17] . Therefore, this formula has been recommended as one of the prescriptions for the COVID-19 treatment and has been proved to be beneficial to cure respiratory tract diseases with symptoms of fever, cough, short breath, and body ache, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism may be related to Regulation of abnormal changes in TNF-α and IL-10 levels. Maxing Shigan Decoction improves the acute lung injury induced by H1N1 by reducing the apoptosis of lung cells and the content of TNF-α in serum [19]. Maxing Shigan Decoction can reduce the expression and release of TNF-α, IL-1β and IL-6 in alveolar lavage uid, improve lung in ammation, and resist acute lung injury caused by in uenza virus infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al identified 67 differentially expressed cellular miRNAs between infection with the H5N1 avian influenza virus (HPAI) and the reconstructed 1918 H1N1 influenza virus (r1918) (2:6) [ 14 ]. Influenza A/FM/1/47 (H1N1)(FM1), is commonly used by Chinese researchers to investigate the immune response and inflammatory pathogenesis during IAV infection, and to evaluate the therapeutic and pharmacological effects of Chinese herbs [ 15 21 ]. However, the FM1-induced general changes in the levels of miRNAs and mRNAs remain unclear.…”
Section: Introductionmentioning
confidence: 99%